Feeding strategy and dietary preference shape the microbiome of epipelagic copepods in a warm nutrient‐impoverished ecosystem. Issue 1 (20th September 2022) - Velasquez, Ximena; Morov, Arseniy R.; Belkin, Natalia; Kurt, Tuba Terbiyik; Rubin‐Blum, Maxim; Tchernov, Dan; Meron, Dalit; Guy‐Haim, Tamar
Abstract: Copepods provide a rich organic microenvironment allowing the settlement and proliferation of microorganisms, forming dynamic microbial hotspots in the oceans. Such symbiotic associations in the plankton were previously hypothesized to be especially developed in warm oligotrophic seas, as they may serve as alternative sources of nutrients in biologically poor waters. Aiming to better understand how copepod microbiomes are shaped in an oligotrophic sea, we characterized microbiota associated with three dominant coastal epipelagic copepod species in the ultra‐oligotrophic Eastern Mediterranean Sea using amplicon sequencing of the 16S rRNA gene . Our results show that copepod‐associated microbial communities were host‐specific rather than determined by seasonal environmental changes. In the filter‐feeding copepod with a tendency to herbivory, Temora stylifera, microbial diversity was low and relatively stable throughout the year. In contrast, omnivorous copepods, the ambush‐feeding Oithona nana, and the mixed‐feeding Centropages ponticus harbored more diverse microbiomes dominated by transient taxa. We suggest that filter‐feeding strategy and narrow food spectrum can limit copepod–microbe interactions, while the ambush and mixed feeding strategies combined with omnivory confer higher microbial diversity. Filter feeders may reduce the recruitment of opportunistic microbes by maintaining high fidelity associations, as indicated by the large number of core taxa in T . stylifera . We underline the importance of the copepod–microbe associations in nutrient‐impoverished ecosystems, based on predicted enrichment of nitrogen metabolism in the core microbiome, mostly during summer when the shallow coastal waters are nitrogen‐depleted. Abstract : Copepods provide a rich organic microenvironment allowing the settlement and proliferation of microorganisms. Such symbiotic associations were previously hypothesized to be especially developed in warm oligotrophic seas. In the ultraoligotrophic Levantine Sea, we found that copepod‐associated microbial communities were host‐specific, suggesting that the filter‐feeding strategy and narrow food spectrum can limit copepod‐microbe interactions, while the ambush and mixed feeding strategies combined with omnivory confer higher microbial diversity.